2019
DOI: 10.1002/hep.30538
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Nonalcoholic Fatty Liver Disease and Reduced Bone Mineral Density in Children: A Meta‐Analysis

Abstract: Recent cross‐sectional studies have examined the association between nonalcoholic fatty liver disease (NAFLD) and bone mineral density (BMD) in children or adolescents, but these have produced conflicting results. We performed a systematic review and meta‐analysis of these published studies to quantify the magnitude of the association, if any, between NAFLD and BMD. We searched publication databases from January 2000 to September 2018, using predefined keywords to identify relevant observational studies conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
(144 reference statements)
0
27
0
Order By: Relevance
“…77 Although obesity duration and severity are also associated with a decreased renal function, 78 NAFLD has been shown to be an independent predictor even after further adjustment for other metabolic risk factors and genetic polymorphisms like I148M (rs738409) of PNPLA3. 57,79 Other comorbidities that NAFLD have been associated with include obstructive sleep apnoea (OSA), 80,81 lower whole bone mineral density 82 and polycystic ovary syndrome. 83 In addition, youth-onset NAFLD has been associated with a variety of psychosocial issues as low self-esteem, psychological distress and poor quality of life.…”
Section: Comorb Id Itie S In Children With Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…77 Although obesity duration and severity are also associated with a decreased renal function, 78 NAFLD has been shown to be an independent predictor even after further adjustment for other metabolic risk factors and genetic polymorphisms like I148M (rs738409) of PNPLA3. 57,79 Other comorbidities that NAFLD have been associated with include obstructive sleep apnoea (OSA), 80,81 lower whole bone mineral density 82 and polycystic ovary syndrome. 83 In addition, youth-onset NAFLD has been associated with a variety of psychosocial issues as low self-esteem, psychological distress and poor quality of life.…”
Section: Comorb Id Itie S In Children With Nafldmentioning
confidence: 99%
“…Other comorbidities that NAFLD have been associated with include obstructive sleep apnoea (OSA), 80,81 lower whole bone mineral density 82 and polycystic ovary syndrome 83 . In addition, youth‐onset NAFLD has been associated with a variety of psychosocial issues as low self‐esteem, psychological distress and poor quality of life 84 .…”
Section: Comorbidities In Children With Nafldmentioning
confidence: 99%
“…A very recent meta-analysis showed that youths with imaging-or biopsy-diagnosed NAFLD had decreased total body or lumbar BMD z scores compared to children without NAFLD (pooled weighted mean difference: −0.48, 95% confidence interval −0.74 to −0.21; I 2 = 55.5%) [88]. Furthermore, a significant difference in total body BMD z scores between children with and without histologically proved NASH was reported (pooled weighted mean difference: −0.27, 95% confidence interval −0.40 to −0.13; I 2 = 0%).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, adults, children, and adolescents with MAFLD have been associated with increased cardiovascular disease (CVD) risk and subclinical atherosclerosis [ 65 ] that has been detected using ultrasound vascular markers [ 64 ]. Of note, children and adolescents with MAFLD/steatohepatitis had lower whole-body or lumbar bone mass density z-scores independent of age, sex, race/ethnicity, and BMI than those without MAFLD [ 66 ].…”
Section: Diagnosis Of Mafld In Children and Adolescentsmentioning
confidence: 99%